2006
DOI: 10.1016/j.ydbio.2006.06.044
|View full text |Cite
|
Sign up to set email alerts
|

SER-1, a Caenorhabditis elegans 5-HT2-like receptor, and a multi-PDZ domain containing protein (MPZ-1) interact in vulval muscle to facilitate serotonin-stimulated egg-laying

Abstract: Serotonin (5-HT) stimulation of egg-laying in Caenorhabditis elegans is abolished in ser-1 (ok345) animals and is rescued by ser-1 expression in vulval muscle. A PDZ binding motif (ETFL) at the SER-1 C-terminus is not essential for rescue, but facilitates SER-1 signaling. SER-1 binds specifically to PDZ domain 10 of the multi-PDZ domain protein, MPZ-1, based on GST pulldown and co-immunoprecipitation. mpz-1 is expressed in about 60 neurons and body wall and vulval muscles. In neurons, GFP-tagged MPZ-1 is punct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 66 publications
6
42
0
Order By: Relevance
“…These results indicated that RMF and RMH might be the cells expressing GFP under the control of the nlp-20 promoter. We further confirmed this result by co-expressing Pnlp-20::gfp with mCherry driven by the promoter of the ser-1 gene, which is known to be expressed in several types of cells including five pairs of head neurons, CEP, RMG, RMH, RMF, and RMD (Xiao et al, 2006). The cells expressing Pnlp-20::gfp co-localized with the reporter Pser-1::mCherry only in RMF or RMH neurons (Figures S3D–S3F).…”
Section: Resultssupporting
confidence: 66%
“…These results indicated that RMF and RMH might be the cells expressing GFP under the control of the nlp-20 promoter. We further confirmed this result by co-expressing Pnlp-20::gfp with mCherry driven by the promoter of the ser-1 gene, which is known to be expressed in several types of cells including five pairs of head neurons, CEP, RMG, RMH, RMF, and RMD (Xiao et al, 2006). The cells expressing Pnlp-20::gfp co-localized with the reporter Pser-1::mCherry only in RMF or RMH neurons (Figures S3D–S3F).…”
Section: Resultssupporting
confidence: 66%
“…To summarize, (1) at least five different amine receptors are involved in the 5-HT stimulation of egg laying, (2) serotonergic input can be both excitatory and inhibitory, (3) serotonergic signaling appears to overlap with other modulatory pathways, and (4) 5-HT appears to function at multiple levels within the egglaying circuit and may modulate both the release of neurotransmitters/neuromodulators and the activity state of vulval muscle. For example, SER-1, SER-7, and the putative 5-HT receptor, SER-5, are all expressed in vulval muscle and the muscle expression of each rescues 5-HT-insensitive egg-laying phenotypes; SER-1 and SER-7 in ser-1 and ser-7 null animals, respectively, and SER-5 in Q5 null animals ( Figure 6; Carnell et al 2005;Hobson et al 2006;Xiao et al 2006). In contrast, the expression of both SER-4 and MOD-1 appears to be exclusively neuronal and neither 5-HT receptor appears to be expressed in vulval muscle or the HSN/VC neurons that control egg laying, suggesting that SER-4 and MOD-1 act upstream to inhibit the egg-laying neurons directly and/or to regulate the release of additional modulators (Mendel et al 1995;Segalat et al 1995;Lackner et al 1999;Bany et al 2003;Moresco and Koelle 2004;Carnell et al 2005;Hobson et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the expression pattern of the mod-1 serotonin-gated Cl ‫מ‬ channel involved in gustatory plasticity has not been described precisely. However, the ser-1 receptor is expressed in the CEP mechanoreceptor neurons, in the RMG, RMH, RMF, and RMD motorneurons, and in pharynx and vulva muscle cells (Xiao et al 2006). Further cell-specific rescue experiments are required to find out which of these cells are involved in gustatory plasticity.…”
Section: Discussionmentioning
confidence: 99%